Pendampingan Pengembangan Soft Skills Ibu-Ibu Mekar di Era Society 5.0 di Kota Semarang - Fidyah Yuli Ernawati; Hendrayanti, Silvia; Junaidi, Achmad; Sukarsono Sukarsono (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the soft skills capacity of the Ibu-Ibu Mekar community in Semarang City to face the demands of the Society 5.0 era. The program was implemented through four stages: needs assessment, participatory planning, training, and mentoring. The methods used included interactive lectures, group discussions, role-play, and contextual practice. The results of the activity showed significant improvements in participants' communication, creativity, collaboration, and problem-solving skills. In addition, several participants began to demonstrate informal leadership roles and greater involvement in community activities. These findings indicate that the experience-based participatory mentoring approach is effective in strengthening women's empowerment and preparing communities for socio-technological change. The program also helped participants develop adaptability to change, increased self-confidence, and facilitated the formation of broader social networks in their communities. Empowering women through soft skills development is expected to create a more resilient community in facing the challenges posed by digital transformation in the Society 5.0 era. This program emphasizes the importance of sustainable soft skills development as a foundation for community resilience in the Society 5.0 era.